Stomach contents of cetaceans in the Alboran Sea and Gulf of Cadiz. - M. Garcia-Polo; Joan Gimenez; J. Luis Mons; Carolina Fernández Maldonado (Frontiers in Marine Science, 2014)
This work describes the diet, through the analysis of stomach contents, of different species of cetaceans in Andalusian waters. Stomachs of 53 specimens, 36 striped dolphins (Stenella coeruleoalba), 13 common dolphins (Delphinus delphis) and 4 Risso's dolphins (Grampus griseus) stranded in the provinces of Cadiz, Huelva, Malaga and Almeria (South Iberian Peninsula) were examined. Strandings were attended by members of the official stranding network of Andalusia. Fourteen of the specimens had no food remains in the stomachs: 9 striped dolphins, 2 common dolphins and 1 Risso´s dolphin. Prey remains consisted mostly of hard structures e.g. fish otoliths, bones and eye lenses, cephalopod jaws and eye lenses and crustaceans exoskeletons. These remains were identified using published guides (e.g. Clarke, 1986; Härkonen, 1986; Xavier & Cherel, 2009) and reference material available at the Centro Oceanográfico in Vigo of the Spanish Institute of Oceanography (IEO). Diet was characterised for each cetacean species using three standard indices, calculated for each category of prey and for group totals: the frequency of occurrence in the stomachs, the number of individuals and the reconstructed prey weight. These indices were also expressed as percentages to allow comparison between cetacean species and groups (e.g. dolphin sex and area of stranding). The results indicate that striped dolphins feed predominantly on small mesopelagic fish, mainly species of the Myctophidae family, although pearlsides (Maurolicus muelleri) were also present. Significant numbers of gobies (Gobiidae) were also found in the stomachs. Other prey identified were hake (Merluccius merluccius), silvery pout (Gadiculus argenteus), bogue (Boops boops) and scads (Trachurus spp.). Because of the degree of erosion of some otoliths they could not be identified to species level. Cephalopods were also found in the stomachs of striped dolphins with specimens of the families Brachioteuthidae, Chiroteuthidae, Sepiolidae, Ommastrephidae and Enoploteuthidae among others being identified from the remains. For common dolphin, myctophids were also important in the diet. Scads were also present. The 3 non-empty stomachs of Risso´s dolphin examined contained only cephalopod beaks (e.g. Todarodes sagittatus, several species of Histioteuthidae, Octopus vulgaris, etc.) confirming the teutophagous diet of this species already reported in other areas (Blanco et al., 2006).